Quality for progress and development - Bose, P.K.; Mukherjee, S.P.; Ramamurthy, K.G. (New Delhi: Wiley Eastern, 1989)
The present volume is a little edited collection of papers (scattered over a wide range of topics) meant for presentation during the Asian congress on quality and Reliability. Papers prepared according to a prescribed format and received by a stipulated date could be accommodated.
Design and development of quality systems -- Quality and economy -- Industrial experimentation and process improvement -- Quality circles -- Education and training in quality and reliability -- Product reliability and maintainability -- Education and training in quality and reliability -- Product reliability and maintainability -- Quality in service sectors -- Developments and implementation of standards -- Measurement standards, calibration and testing -- Accreditation/certification systems -- product liability and consumer protection -- Software quality and reliability -- Agricultural productivity with particular reference to quality of inputs -- statistical methods in quality and reliability -- Papers received late.
Papers presented at the First Asian congress on Quality and Reliability
Keywords: Quality Control; Progress and development